Besedotvorje: Teoretično, praktično in didaktično - Stramljič Breznik, Irena (University of Maribor Press, 2020)
Word Formation: Theoretical, Practical and Didactic Aspects. Monograph Word Formation: Theoretical, Practical and Didactic Aspects focuses on the topic of word formation in the Slovene language from the different perspectives which are mentioned in its title and which present the basis for the division into three chapters. The first chapter is theoretical in nature and provides a concise overview of the diverse typology of complex words and theoretical approaches to current studies of Slovene word formation. Attention is also given to the metaphorical origins of word formation terminology in Slovene grammars of the 19th century. At the same time, the word formation potential of certain types of borrowed words in contemporary Slovene is compared with the word formation potential of their domestic equivalents. The definition of primary morphemic functions of multifunctional morphemes is possible only through observations of their development from a diachronic perspective, from the origins of the Slovene literary language to the use of language today. The third chapter focuses on the role of word formation in the teaching of Slovene as the first or second language at different levels of education. To date, this topic has received very little attention in scholarly literature. This has to be changed, since word formation is one of the most vital linguistic functions keeping language alive in all the different roles it performs in diverse areas of life.